Leveraging AI-driven nudge theory to enhance hand hygiene compliance: paving the path for future infection control - Bhattacharjee, Samiksha; Bhattacharya, Sudip (Frontiers in Public Health, 2025)
Hand hygiene is critical for preventing infections, yet maintaining compliance remains challenging across healthcare, schools, and communities. Despite strong evidence, lapses occur due to cognitive barriers, understaffing, limited resources, and antimicrobial resistance. Behavioral science highlights factors like time constraints and cognitive biases affecting adherence, with compliance rates as low as 40%. Nudge theory, developed by Thaler and Sunstein, offers promising solutions by using subtle interventions, like visual or auditory cues, to encourage hand hygiene without imposing strict regulations. Recent innovations integrate artificial intelligence (AI) with nudges, enhancing compliance through real-time feedback. AI-powered systems, such as smart dispensers and wearable devices, provide reminders using visual or auditory cues at critical moments. For example, dispensers may light up or chime when a healthcare worker enters a patient’s room, prompting hand hygiene. Studies show these AI-driven interventions significantly improve compliance, with rates increasing by up to 30% in some cases. AI can also analyze patterns of non-compliance, deploying personalized nudges during high-risk periods. Combining nudge theory with gamification, such as team-based competitions and rewards, further reinforces positive habits. However, implementing AI solutions in countries like India faces challenges, including limited resources, resistance to new technologies, and cultural barriers. Despite hurdles, integrating AI-driven nudges with behavioral strategies has the potential to transform hand hygiene practices. This approach fosters accountability, reduces infection rates, and ensures safer patient care by embedding compliance into daily routines, paving the way for sustainable improvements in infection control.